1981
DOI: 10.1063/1.441085
|View full text |Cite
|
Sign up to set email alerts
|

VUV fluorescence following photodissociation of N2O at 193 nm

Abstract: Photolytic studies performed at 193 nm demonstrate that NO in the highly excited D(v = 1,5) and E(v = 0) states is generated from N2O during irradiation in three sequential steps involving photodissociation, chemical reaction, and photoexcitation. The resulting NO fluorescence (160–230 nm) was analyzed with a system of rate equations, and the temporal behavior, intensity dependence, and pressure dependence were found to be consistent with a simple kinetic model. The quenching coefficient of NO by N2, Ar, and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Zavelovich et al [13] studied VUV fluorescence following photodissociation of N 2 O at 193 nm with an output energy of ∼80 mJ per pulse in the N 2 O pressure range of 133-26,600 Pa. They found that the dependence of the fluorescence intensity of NO emissions on laser intensity was linear even under unfocused conditions.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Zavelovich et al [13] studied VUV fluorescence following photodissociation of N 2 O at 193 nm with an output energy of ∼80 mJ per pulse in the N 2 O pressure range of 133-26,600 Pa. They found that the dependence of the fluorescence intensity of NO emissions on laser intensity was linear even under unfocused conditions.…”
Section: Resultsmentioning
confidence: 96%
“…6(b). No significant enhancement of NO + On the basis of the above findings and known N 2 O photolysis under 193 nm [12][13][14], it was concluded that N 2 O decomposition diluted in N 2 initiates from selective one-photon-excitation of N 2 O followed by dissociation into O ( 1 D) and N 2 :…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations